Developing Teachers Through “Teacher Clinic” - Rahmawati, Ganes Devita; Isnaini, Linda; Maulia, Vina Citra Tri (EDULIA: English Education, Linguistic and Art Journal, 2024)
This study aims to find out how the "Teachers Clinic" program runs to teacher development. This study is important because teacher development can find out the obstacles faced by teachers and improve teacher performance. "Teachers Clinic" is one of the programs created by the language institute as a teacher development program. Through this program, teachers have the opportunity to discuss difficulties when teaching, receive input and improve teacher performance in teaching. The research method used in this research is qualitative design. This research was conducted through face-to-face interviews with the participant as the Branch Manager of a course institution. The data obtained from the interviews were analyzed qualitatively by transcribing and describing the data. The result showed the “Teacher Clinic” became a promising program as an effort in developing teacher quality. This program involves three stages including: the sharing stage, the observation stage, and the evaluation stage. Therefore, the finding demonstrated that teachers are helped with this program because it solves the teachers’ problems during teaching practice. It was clear that the “Teacher Clinic” program assists in developing teacher growth. Furthermore, this study suggests that educational institutions consider adopting the "Teacher Clinic" in their professional development programs to enhance teaching quality. In addition, integrating the "Teaching Clinic" program can contribute significantly to teacher growth and the overall improvement of educational standards. Keywords: Process, Teacher Clinic, Teacher Development